Inflation and growth: Explaining a negative effect - Gillman, M.; Harris, Mark; Mátyás, L. (2009)
Kormendi and McGuire (1985) document a negative eﬀect of inﬂation on economic growth for a cross-section of 47 countries during the period 1950-1977. Recent panel evidence such as Barro’s (2001) strengthens the support for such a negative eﬀect. In qualiﬁcation, Khan and Senhadji (2001), Ghosh and Phillips (1998), and Judson and Orphanides (1996) all ﬁnd a signiﬁcant negative inﬂation-growth eﬀect above a certain “threshold” value of the inﬂation rate, and no signiﬁcant eﬀect below the threshold value, without using instrumental variables and with diﬀerences found between less and more developed country samples. Further the above threshold negative eﬀect that they ﬁnd is signiﬁcantly non-linear whereby the marginal eﬀect is stronger at lower inﬂation rates than at higher ones; see also Fischer (1993).